Pengaruh Kompensasi, Motivasi, dan Lingkungan Kerja Sebagai Kepuasan Kerja Terhadap Kinerja Karyawan - Verina Dhiva Azzahra (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The study aims to find out the impact on compensation, motivation, and the working environment in creating job satisfaction which in turn is expected to have a positive impact on employee performance. The method used in this research is a quantitative method with a descriptive analysis approach. The data was collected through the distribution of online questionnaires using the Microsoft Forms platform. The survey respondents consisted of 101 employees of different age ranges in one company. The data obtained from the questionnaire is measured using a Likert scale from one to five, which allows respondents to give the level of agreement or disagreement with statements related to compensation, motivation, work environment, job satisfaction, and employee performance. Data analysis is done using several steps, including the Outer Model and the Inner Model. Outer Models involve calculations of Convergent Reliability, Discriminant Validity, Composite Reliability, and Cronbach's Alpha. This aims to ensure the validity and reliability of the data used in the research. Meanwhile, the Inner Model involves statistical T, R-Square, f-square and VIF calculations using the SmartPLS (Partial Least Square) analysis tool version 4.0.9.3. Research results show that compensation, motivation, and the working environment have a positive and significant influence on employee job satisfaction.